Aplicação da metodologia pesquisa-ação no projeto de extensão na comunidade: empreendedorismo feminino de impacto social na ocupação Bela Vista do Juá. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The present work evaluates the effects produced by the Action Research methodology in the execution of the extension project in the community Feminine Entrepreneurship with Social Impact: planting a seed capital in the Bela Vista of Juá occupation (PEC JUÁ). For this purpose, the research has specific objectives, to present the Social Impact Feminine Entrepreneurship project in the Bela Vista of Juá occupation as an extension action of UFopa, detailing the stages of the project, describing the Action Research methodology experienced in conducting the project, and identifying advances and limitations of the Action Research methodology experienced in the management of PEC JUÁ. The theoretical framework contextualizes the history of university extension, emphasizing the bases of legislation that guide the construction of extension actions in Brazilian universities. The study can be characterized as action research, empirical, qualitative, descriptive, carried out through bibliographical and documentary research, participant observation techniques and interviews. As result, the project generated significant effects, both in the lives of the participants, promoting a valuable contribution to the development of their entrepreneurial activities, and for the students and teacher, members of the project team, as it provided the opportunity to apply knowledge acquired in the classroom, thereby putting into practice the foundations of university extension.
Keywords: Pesquisa-Ação; Extensão Universitária; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS